Cardiac mortality after radiotherapy, chemotherapy and endocrine therapy for breast cancer: Cohort study of 2 million women from 57 cancer registries in 22 countries - Henson, KE; McGale, P; Darby, SC; Parkin, DM; Wang, Y; Taylor, CW (Wiley, 2020)
Comparisons of patients receiving different cancer treatments reflect the effects of both treatment and patient selection. In breast cancer, however, if radiotherapy decisions are unrelated to laterality, comparisons of left‐sided and right‐sided cancers can demonstrate the causal effects of higher‐versus‐lower cardiac radiation dose. Cardiac mortality was analysed using individual patient data for 1,934,248 women with breast cancer in 22 countries. The median date of diagnosis was 1996 and the interquartile range was 1987–2002. A total of 1,018,505 women were recorded as irradiated, 223,077 as receiving chemotherapy, 317,619 as receiving endocrine therapy and 55,264 died of cardiac disease. Analyses were stratified by time since breast cancer diagnosis, age at diagnosis, calendar year of diagnosis and country. Patient‐selection effects were evident for all three treatments. For radiotherapy, there was also evidence of selection according to laterality in women irradiated 1990 or later. In patients irradiated before 1990, there was no such selection and cardiac mortality was higher in left‐sided than right‐sided cancer (rate ratio [RR]: 1.13, 95% confidence interval 1.09–1.17). Left‐versus‐right cardiac mortality RRs were greater among younger women (1.46, 1.19, 1.20, 1.09 and 1.08 after cancer diagnoses at ages <40, 40–49, 50–59, 60–69 and 70+ years, 2ptrend =0.003). Left‐versus‐right RRs also increased with time since cancer diagnosis (1.03, 1.11, 1.19 and 1.21 during 0–4, 5–14, 15–24 and 25+ years, 2ptrend =0.002) while for women who also received chemotherapy, the left‐versus‐right RR was 1.42 (95% confidence interval 1.13–1.77), compared to 1.10 (1.05–1.16) for women who did not (2pdifference= 0.03). These results show that the relative increase in cardiac mortality from cardiac exposure during breast cancer radiotherapy given in the past was greater in younger women, lasted into the third decade after exposure and was greater when chemotherapy was also given.